2012
DOI: 10.1002/j.1532-2149.2012.00188.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased cold and heat pain thresholds influence the thermal grill illusion in schizophrenia

Abstract: CPT and HPT, as well as temperature differentials for the perception of the TGI were increased in patients with schizophrenia as compared to controls. Similar to visual illusions, in which reduced contrast sensitivity has been shown to alter the perception of illusions, the discriminatory somatosensory deficit, which is reflected in higher CPT and HPT as well as the previously reported increased warmth perception thresholds, might account for the attenuation of TGI in patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 40 publications
4
32
1
1
Order By: Relevance
“…Although the largest pain response to the TGI was reported when the thermal grill configuration was 18°C/42°C, the thermal grill did not produce a very painful stimulus in pain‐free participants (median 2 on an 11‐point NRS, interquartile range 1 to 5), being below 4 (out of 10), which is generally accepted as the minimum for clinically relevant pain [55]. The reported pain intensity in our study is similar to previous studies investigating the TGI in pain‐free participants, where similar thermal grill configurations produced pain intensity ratings between 7 mm and 47 mm on a 100‐mm VAS [6,8–11,15,16,18,20,21]. Instead, the thermal grill produced an altered sensory experience in our study that manifested as an aversive heat stimulus (approx.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Although the largest pain response to the TGI was reported when the thermal grill configuration was 18°C/42°C, the thermal grill did not produce a very painful stimulus in pain‐free participants (median 2 on an 11‐point NRS, interquartile range 1 to 5), being below 4 (out of 10), which is generally accepted as the minimum for clinically relevant pain [55]. The reported pain intensity in our study is similar to previous studies investigating the TGI in pain‐free participants, where similar thermal grill configurations produced pain intensity ratings between 7 mm and 47 mm on a 100‐mm VAS [6,8–11,15,16,18,20,21]. Instead, the thermal grill produced an altered sensory experience in our study that manifested as an aversive heat stimulus (approx.…”
Section: Discussionsupporting
confidence: 83%
“…In support of this hypothesis, analyses revealed that the increased temperature differential between the cool and warm bars required for the perception of the TGI in patients with MDD was mainly driven by patients' significant decrease in their CPTs [21]. Similar to patients with MDD, CPTs were significantly decreased, while HPTs as well as thermal grill thresholds were significantly increased in patients with schizophrenia compared with healthy controls [20]. Although cold and warm detection thresholds were not investigated in Boettger and colleagues' [20] study, Jochum and colleagues [54] previously demonstrated that patients with schizophrenia had elevated warm detection thresholds compared with controls, thereby overall supporting the above hypothesis for increased thermal grill thresholds in patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The responses point to the ability of the brain to have a ‘pain experience’ in these patients without obvious physical pain. This is of particular interest since schizophrenic patients have a decreased sensitivity to experimental pain (Boettger et al, 2012) and expression of pain (Martins et al, 2011). The basis for such delusions may relate to alterations in dopaminergic signaling involved in salience function (Heinz and Schlagenhauf, 2010).…”
Section: Emotional Pain Without Physical Pain and Pain Relief Withmentioning
confidence: 99%